Fakta Kemanusiaan dalam Novel Sayyidat Al-Qamar Karya Jokha Alharthi - Hidayah, Alya Nur; Qonit, Ahmad; Solihin, Ihin (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
The novel Sayyidat al-Qamar by Jokha Alharthi represents modern Arabic literature that captures the historical reality of Oman, particularly the issues of slavery, limited access to education for women, and marriage traditions rooted in patriarchal values. This study aims to examine humanitarian facts, encompassing both individual and social dimensions, through Lucien Goldmann’s genetic structuralism approach. A Descriptive Qualitative Method was employed, using thematic classification of selected excerpts that depict inner conflicts and social contexts, with close reading and note-taking as the primary data collection techniques. The findings reveal that the novel’s social realities shape how the characters think, act, and respond to their surroundings. The individual facts emerge through characters’ emotional struggles and inner conflicts, while the social facts are reflected in the portrayal of slavery, educational inequality, and restrictive marriage practices in pre-reform Oman. Therefore, Sayyidat al-Qamar serves not only as a literary work but also as a reflective medium that highlights the dialectical relationship between social structure, history and individual consciousness within modern Arab society.Keywords - Arabic Novel, Genetic Structuralism, Human Facts.